m6A: An Emerging Role in Programmed Cell Death - Tang, Fajuan; Chen, Lin; Gao, Hu; Xiao, Dongqiong; Li, Xihong (Frontiers in Cell and Developmental Biology, 2022)
Programmed cell death is an active extinction process, including autophagy, ferroptosis, pyrolysis, apoptosis and necroptosis. These processes are all regulated by their own independent signal pathways and regulatory pathways. N6-methyladenosine is a reversible RNA modification and regulated dynamically by methylases and demethylases to determine the fate and function of RNA under the action of RNA methylation modification recognition enzymes. Adenosine undergoes methylation modification under the action of methylases (writers) to achieve installation, and is removed under the action of demethylases (erasers). The RNA base site at which m6A is modified is recognized by specialized enzymes (readers) which regulate downstream mRNA output, translation, degradation, and other processes. Regulated factors including writers, erasers and readers promote or inhibit programmed cell death via up-regulating or down-regulating downstream targets in a m6A-dependent manner to participate in the process of disease. In this review, we summarize the mechanisms of N6-methyladenosine with particular reference to its role in programmed cell death.